SOCIO-PSYCHOLOGICAL ADAPTATION OF THE MODERN TEACHER TO WORLD CHANGES - Pavlyk, Natalia Vasylivna (Distance Education in Ukraine: Innovative, Normative-Legal, Pedagogical Aspects, 2025)
The article is devoted to the analysis of the concepts of «adaptation», «adaptability», the definition of their types, structure, the definition of psychodiagnostic tools for the study of the features of the socio-psychological adaptation of a personality to global world changes. The author presents a theoretical analysis of the essence of the concept of "social-psychological adaptation", which is considered as a property of personality that characterizes his resistance to environmental conditions and the level of adaptation to them. Socio-psychological adaptation is a multifaceted process of adapting the human psyche and behavior to the conditions of the social environment. The article presents various types of personality adaptation (mental, psychological, social, socio-psychological, professional, cultural) and detailed psychological mechanisms, determinants and levels of development of social-psychological maladaptation of the personality.